ENHANCING SURGICAL HAND HYGIENE COMPLIANCE AMONG HEALTHCARE WORKERS AT EMCAS PLASTIC SURGERY HOSPITAL DURING 2026-2027 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of surgical hand hygiene compliance among healthcare staff at EMCAS Plastic Surgery Hospital in 2025 and to propose some solutions to enhance surgical hand hygiene compliance among healthcare staff at EMCAS Plastic Surgery Hospital in the period 2026-2027.Methods: The project observed 90 surgical hand hygiene sessions of 45 medical staff including doctors, nurses, and technicians participating in surgeries using the surgical hand hygiene checklist during the period from May to July 2025. At the same time, 4 in-depth interviews were conducted and 2 group discussions were organized with relevant subjects through pre-prepared in-depth interview and group discussion guidelines.Results and conclusion: The rate of staff compliance with the time to perform the surgical hand hygiene procedure was 53.3%, and compliance with the content of the surgical hand hygiene procedure was 42.2%. Ensuring adequate and always ready equipment and supplies for surgical hand hygiene; Raising awareness and skills in surgical hand hygiene for medical staff; Developing documents and implementing communication to raise awareness and improve surgical hand hygiene compliance practices among medical staff; Increasing the frequency of periodic monitoring and evaluation; Investing in upgrading and perfecting the camera system to monitor compliance.
Keywords: Healthcare workers, patients, compliance, surgical hand hygiene, hand hygiene, surgery.